A Comparison between Diet, Exercise, and Combined Intervention in Women with Polycystic Ovarian Syndrome (A Systematic Review for The Anthropometric, Metabolic, Psychological, and Hormonal Parameters) - Rizky Ika Nahdiah (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Lifestyle changes are first-line treatments for Polycystic Ovary Syndrome (PCOS), but the comparative efficacy of various modalities remains unclear.Objective: This systematic review compares the effects of diet (D), exercise (E), and combined interventions (ED) on PCOS manifestations.Methods: A systematic search of PubMed, ScienceDirect, and Springer (2021–2025) identified 9 RCTs involving 418 women. Outcomes included anthropometric, metabolic, psychological, and hormonal parameters.Results: Dietary intervention (D) produced the greatest improvements in insulin sensitivity (HOMA-IR, fasting glucose), lipid profiles (TC, LDL, TG), and hormonal balance (SHBG, LH). Combined therapy (ED) was most effective for reducing BMI and increasing HDL. Conversely, exercise alone (E) was most effective at reducing depression and anxiety scores. No significant changes were observed in WHR or FSH. Discussion: Diet serves as a metabolic anchor by addressing hyperinsulinemia, while exercise catalyzes mental health benefits. The synergy of ED optimizes body composition and cardiovascular health.Conclusion: PCOS management should be personalized, prioritizing diet for metabolic control and exercise for psychological well-being. A combined approach offers the most comprehensive benefits for body composition and long-term health.Perbandingan antara Diet, Olahraga, dan Intervensi Kombinasi pada Wanita dengan Sindrom Ovarium Polikistik (Sebuah Tinjauan Sistematis terhadap Parameter Antropometri, Metabolik, Psikologis, dan Hormonal)AbstrakPendahuluan: Perubahan gaya hidup merupakan lini pertama pengobatan Polycystic Ovary Syndrome (PCOS), namun efektivitas perbandingan berbagai modalitas masih belum jelas.Tujuan: Tinjauan sistematis ini membandingkan dampak diet (D), olahraga (E), dan intervensi kombinasi (ED) terhadap manifestasi PCOS.Metode: Tinjauan sistematis pada PubMed, ScienceDirect, dan Springer (2021 – 2025) mengidentifikasi 9 studi RCT yang melibatkan 418 wanita. Parameter yang diukur meliputi antropometri, metabolik, psikologis, dan hormonal.Hasil: Intervensi diet (D) memberikan perbaikan terbesar pada sensitivitas insulin (HOMA-IR, glukosa puasa), profil lipid (TC, LDL, TG), dan keseimbangan hormonal (SHBG, LH). Terapi kombinasi (ED) paling efektif untuk penurunan BMI dan peningkatan HDL. Sebaliknya, olahraga mandiri (E) menunjukkan efikasi tertinggi dalam mengurangi skor depresi dan kecemasan. Tidak ditemukan perubahan signifikan pada WHR atau FSH pada semua kelompok.Diskusi: Diet berperan sebagai jangkar metabolik dalam mengatasi hiperinsulinemia, sementara olahraga berfungsi sebagai katalis kesehatan mental. Sinergi ED mengoptimalkan komposisi tubuh dan kesehatan kardiovaskular.Kesimpulan: Penatalaksanaan PCOS harus dipersonalisasi; memprioritaskan diet untuk kontrol metabolik dan olahraga untuk kesejahteraan psikologis. Pendekatan kombinasi menawarkan manfaat paling komprehensif bagi komposisi tubuh dan kesehatan jangka panjang.